Comparison of Two Instruments to Assess the Impact of Cachexia on Quality of Life in Women with Cervical Cancer. - Luvián-Morales, Julissa; Galvan-Cota, Luis Daniel; Galvan-Cota, Luis David; Castro-Eguiluz, Denisse; Oñate-Ocaña, Luis F. (Nutrition & Cancer, 2026)
Cancer-associated cachexia (CAC) is common in cervical cancer (CC) patients. This condition affects the Health-related quality of life (HRQL). This study aims to assess the impact of CAC on HRQL, comparing the Quality of Life Questionnaire (QLQ) QLQ-C30/QLQ-CAX24 and the Functional assessment of anorexia/cachexia therapy (FAACT) instruments. A cohort of CC patients answered the QLQ-C30/QLQ-CAX24 and the FAACT instruments between October 2020 and October 2021. The psychometric/clinimetric characteristics of the instruments were compared. 244 CC patients were included in the study. Correlations between scales ranged from 0.008 to 0.81. The summary score of QLQ-C30 correlated well with the FAACT total score (r = 0.684) and the FAACT Physical Well-being subscale (r = 0.81). The correlation with five nutritional parameters and prognostic indices was poor (r < 0.364). Most symptom scales of the QLQ-CAX24 presented a floor effect, and those of the FAACT did not. The Nausea/vomiting score of the QLQ-C30, and the Loss of control and Forced to eat scales of the QLQ-CAX24 were independently associated with overall survival. The QLQ-C30/QLQ-CAX24 and FAACT instruments differ substantially, but some scales are comparable. We propose an algorithm to select the appropriate instrument to asses HRQL for a research protocol.